An application of the concept of entropy to problems of detecting a signal in the noise - Dobrushin, R. L.; Pinsker, M. S.; Shiryaev, A. S. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Л. Добрушин, М. С. Пинскер, А. Н. Ширяев. Применение понятия энтропии в проблемах обнаружения сигнала в фоне шума R. L. Dobrušinas, M. S. Pinskeris, A. S. Širiajevas. Entropijos sąvokos taikymas signalo sugavimo problemose triukšmo fone